Pengaruh Kepemimpinan Etis Terhadap Keterlibatan Karyawan dan Perilaku Organisasi - Endang Prihatin; Defifi Ismiyati; Rizka Irawan (Pusat Riset dan Inovasi Nasional, 2021)
This study examines the impact of ethical leadership on both employee engagement and organizational behavior through a multilevel analysis. Ethical leadership, characterized by integrity, fairness, and ethical decision-making, is increasingly recognized as a crucial factor in shaping organizational outcomes. Drawing upon data from multiple levels within organizations, including individual employees and their respective teams, this research employs statistical techniques to explore the intricate relationships between ethical leadership, employee engagement, and organizational behavior. Findings suggest that ethical leadership positively influences both employee engagement and organizational behavior at both individual and group levels. Moreover, the study elucidates the mediating role of employee engagement in the relationship between ethical leadership and organizational behavior, underscoring the importance of fostering ethical leadership behaviors for promoting a positive organizational culture and enhancing employee contributions beyond formal role requirements.